Time to Refocus Assessment of Vision in Older Adults? Contrast Sensitivity but Not Visual Acuity Is Associated with Gait in Older Adults - Finucane, Ciaran; Kenny, Rose (My University, 2017)
Background: The relationship between measures of visual function and gait related risk factors for falls is unclear. In this study, we examine the relationship between visual function (visual acuity [VA] and contrast sensitivity [CS] at multiple spatial frequencies) and quantitative spatiotemporal gait, using a large, nationally representative sample of community dwelling older adults. Methods: Participants aged 50 and over were recruited as part of The Irish Longitudinal Study on Ageing (TILDA). VA was measured with the LogMAR chart according to the Early Treatment of Diabetic Retinopathy Study protocol. CS was measured at five spatial frequencies ranging 1.5 to 18 cycles per degree (cpd) using the Functional Acuity Contrast Test. Gait speed, cadence, and stride length were measured using the GAITRite system. Multivariate analysis examined associations between gait and visual performance parameters adjusting for socioeconomic, physical, cognitive, and mental health covariates. Results: Data from 4,678 participants were analyzed (age 61.7 ± 8.3 years, 54.1% woman). Poorer CS at 1.5 cpd and 3.0 cpd (low spatial frequency) was independently associated with decreased stride length (CS at 1.5 cpd: β = .031; p = .001 and CS at 3.0 cpd: β = .020; p = .001) but not cadence or gait speed. There was no evidence of an association between VA and any of the gait variables considered (p > .05). Conclusion: Reduced CS, at low spatial frequencies, is independently associated with shorter stride length, while VA is not associated with any gait measures. This evidence suggests that it may be necessary to consider refocus of the assessment of vision to include the most appropriate measures.
Keywords: Contrast sensitivity, Falls, Visual acuity